2021
DOI: 10.1371/journal.pone.0253722
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of palbociclib and ribociclib in patients with estrogen and/or progesterone receptor positive, HER2 receptor negative metastatic breast cancer in routine clinical practice

Abstract: Background There is scant data from India on efficacy and safety of palbociclib and ribociclib in routine clinical practice. Methods This retrospective, observational, single institution study included patients with estrogen and/or progesterone receptor positive and human epidermal growth factor receptor 2 (HER2) negative metastatic breast cancers, who received palbociclib or ribociclib with any partner endocrine therapy in any line of treatment between January 2016 and June 2019. Data were analyzed for prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
11
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 15 publications
2
11
3
Order By: Relevance
“…Only 27 (19%) patients were premenopausal at the time of presentation, which was similar to the IRIS study [8]. Ductal carcinoma was the most common histology in our study, similar to that reported by Rath et al [9]. Bone-only metastases were seen in 32 (23%) patients.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Only 27 (19%) patients were premenopausal at the time of presentation, which was similar to the IRIS study [8]. Ductal carcinoma was the most common histology in our study, similar to that reported by Rath et al [9]. Bone-only metastases were seen in 32 (23%) patients.…”
Section: Discussionsupporting
confidence: 91%
“…The median OS of our study population was 29.7 months, more than 27.1 months reported by Rath et al [9]. In the same study, the median OS in the first-line setting was not reached, while it was 39.9 months in our study [9]. These two differences can be attributed because the overall study population differed in both studies.…”
Section: Discussioncontrasting
confidence: 60%
See 3 more Smart Citations